The Oxford Handbook of Andrew Marvell - Dzelzainis, Martin; Holberton, Edward Ed. (Oxford : Oxford University Press, 2019)
The Oxford Handbook of Andrew Marvell is the most comprehensive and informative collection of essays ever assembled dealing with the life and writings of the poet and politician Andrew Marvell (1621-78). Like his friend and colleague John Milton, Marvell is now seen as a dominant figure in the literary landscape of the mid-seventeenth century, producing a stunning oeuvre of poetry and prose either side of the Restoration. In the 1640s and 1650s he was the author of hypercanonical lyrics like 'To His Coy Mistress' and 'The Garden' as well as three epoch-defining poems about Oliver Cromwell. After 1660 he virtually invented the verse genre of state satire as well as becoming the most influential prose satirist of the day-in the process forging a long-lived reputation as an incorruptible patriot. 0Although Marvell himself was an intensely private and self-contained character, whose literary, religious, and political commitments are notoriously difficult to discern, the interdisciplinary contributions by an array of experts in the fields of seventeenth-century literature, history, and politics gathered together in the Handbook constitute a decisive step forward in our understanding of him. They offer a fully-rounded account of his life and writings, individual readings of his key works, considerations of his relations with his major contemporaries, and surveys of his rich and varied afterlives. Informed by the wealth of editorial and biographical work on Marvell that has been produced in the last twenty years, the volume is both a conspectus of the state of the art in Marvell studies and the springboard for future research.